Method for preparing spherical Al2O3 nanocrystal grains at low temperature

By adsorbing boehmite in porous materials and replacing aluminoxane precursors with carboxylic acid for low-temperature pyrolysis, the problems of uneven particle size distribution and difficult size regulation of spherical nanoalumina powder in the prior art are solved, and spherical nanoalumina powders are prepared at low temperatures, simplifying the preparation process and improving the dispersion and morphological stability of the powder.

CN119528189APending Publication Date: 2025-02-28HENAN JIYUAN BROTHER MATERIAL CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411655312.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

In the prior art, when preparing spherical nanoalumina powders, there are problems such as uneven particle size distribution, difficult size regulation, and high-temperature sintering, which lead to poor dispersion of powder and morphology destruction.

Method used

Boehmite is used as an aluminum source to prepare porous materials containing carboxyl groups by specific methods. Boehmite is adsorbed in the pores by using the adsorption properties of the porous materials, and combined with carboxylic acid to replace the aluminoxane precursor, and low-temperature pyrolysis is performed to prepare spherical nanoalumina.

Benefits of technology

The preparation of spherical nanoalumina with controllable size is realized at low temperatures, avoiding agglomeration during sintering, simplifying the preparation process, and no gradient heating procedure is required.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119528189A_ABST
    Figure CN119528189A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of alumina powder preparation, and particularly relates to a method for preparing spherical Al2O3 nanocrystals at low temperature, which mainly comprises the following steps: S1, preparing a porous material; s2, preparing a carboxyl precursor; s3, preparing an aluminum oxide precursor; and S4, calcining the precursor to obtain the spherical nano aluminum oxide. The preparation method comprises the following steps: grafting carboxyl into a porous material to obtain a carboxyl precursor material, adsorbing boehmite with a proper particle size on the surface of a pore channel by virtue of a relatively large specific surface of the porous material, replacing an aluminoxane precursor with carboxylic acid, and decomposing or carbonizing the carboxyl precursor by virtue of subsequent one-step high-temperature pyrolysis, so as to obtain the porous material. Partially decomposed long-chain organic groups or degraded carbides thereof can inhibit too fast growth of aluminum oxide particles and reduce the transformation temperature of an alpha-Al2O3 phase, and spherical nano alpha-Al2O3 with the size of 20-30 nm can be obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of alumina powder preparation, and in particular relates to a method for preparing spherical Al2O3 nano-crystals at low temperature. Background Art

[0002] As the most stable crystal structure of alumina, nano-α-Al2O3 has high chemical stability and high melting point. Due to its excellent properties such as good insulation, high mechanical strength and high hardness, it is widely used in ceramics, electronics, and chemical industries. Studies have shown that the performance of Al2O3 products is not only related to the crystal form, but also has a great relationship with the microscopic morphology, size and dispersibility of the Al2O3 powder particles. Due to the differences in raw materials and preparation processes, there are many morphologies of Al2O3 powder, including rod-shaped, flower-shaped, flake-shaped, spherical and spinning-shaped. Among the many crystal forms and morphologies of Al2O3, spherical nano-α-Al2O3 powder can significantly improve the performance of the product due to its excellent properties of regular morphology, high bulk density, high fluidity and good sintering characteristics. When the size of powder particles is reduced to the nanoscale (<100nm), the proportion of surface atoms in the particles increases significantly, giving nanomaterials many new properties, such as quantum size effect, volume effect and surface effect. These new properties enable nanomaterials to exhibit excellent performance in many fields such as surface coatings, electronic wiring, composite materials, biomedicine and optical devices.

[0003] Domestic and foreign scholars have conducted a lot of research on the preparation methods of spherical nano α-Al2O3 powders. At present, the commonly used preparation methods of spherical nano alumina mainly include spray pyrolysis, homogeneous precipitation, microemulsion and high-energy ball milling. However, the alumina powder obtained by the above-mentioned related preparation methods has uneven particle size distribution and is not easy to control the size. On the other hand, it requires a very high temperature to complete the crystal transformation of α-Al2O3. High-temperature calcination easily causes sintering between spherical powders, resulting in poor powder dispersion and destruction of the spherical morphology. Prior art CN103663523B A spherical alumina nanocrystal and a preparation method thereof discloses that the organic metal precursor dry gel of carboxyl-substituted aluminoxane is subjected to programmed temperature pyrolysis and the organic molecular chain segments are removed to obtain spherical alumina nanocrystalline particles. The prepared spherical alumina nanocrystalline particles have a particle size of 5 to 30 nm; the crystal phase is α phase. The method does not require special reaction equipment, the operation process is simple, and it is easy to scale up the preparation. However, on the one hand, the alumina prepared by this scheme still has a certain degree of particle agglomeration during the sintering process and needs to be assisted by a specific gradient heating program. On the other hand, the alumina powder prepared by this invention has the defect that its size is difficult to control. Summary of the invention

[0004] In order to solve the technical problems mentioned in the above background technology, the present invention uses boehmite as an aluminum source, adopts a specific method to prepare a porous material containing carboxyl groups, utilizes the adsorption properties of the porous material to adsorb boehmite in the pores, utilizes carboxylic acid to replace the aluminoxane precursor, and obtains size-controllable spherical nano-alumina through a subsequent one-step pyrolysis.

[0005] The method for preparing spherical Al2O3 nanoparticles at low temperature in the present invention mainly comprises the following steps:

[0006] S1: Preparation of porous materials;

[0007] S2: Preparation of carboxyl precursors;

[0008] S3: Preparation of alumina precursor;

[0009] S4: The precursor is calcined to obtain spherical nano-alumina.

[0010] Furthermore, the porous material is prepared by suspension polymerization, and the mass ratio of oil phase to water phase in the suspension polymerization system is 1:3.

[0011] Furthermore, the polymerizable monomers in the oil phase are divinylbenzene and methyl methacrylate, the initiator is benzoyl peroxide, the porogen is n-heptane, the mass ratio of divinylbenzene to methyl methacrylate is 0.5-1:1, the amount of initiator is 0.1-0.5% of the total mass of the polymerizable monomers, and the mass ratio of the porogen to the polymerizable monomers is 2-3:1.

[0012] During the polymerization process, the presence of the porogen leads to incompatibility between the polymer phase and the porogen phase, thereby inducing phase separation. This phase separation is the basis for forming a pore structure. After phase separation, the porogen is removed, leaving pores. The type and amount of the porogen can greatly affect the size and distribution of the pores. The porogen used in this application is a non-good solvent, which will cause the system to phase separate earlier, thereby forming a larger pore volume and average pore size. If other solvents are used, it is difficult to achieve the expected pore size and distribution of the present invention, thereby affecting the size screening effect of the pore size.

[0013] Furthermore, the aqueous phase includes 5% PVA as a dispersant, and the weight of the dispersant accounts for 8-10% of the aqueous phase.

[0014] Furthermore, the suspension polymerization stirring speed is 280-300 r / min, the polymerization temperature is 76-78° C., and the temperature is kept for 4-6 hours. After the reaction is completed, the material is washed with ethanol to obtain a spherical porous material.

[0015] The stirring speed during suspension polymerization will significantly affect the particle size of the final product. In the present invention, a rotation speed higher than that of ordinary suspension polymerization is used to obtain a porous material with a smaller particle size, and a smaller particle size helps it to be evenly mixed with the boehmite solution.

[0016] Furthermore, the preparation method of the carboxyl precursor in step S2 is: the spherical porous material obtained in step S1 is fully swollen in toluene, after removing the solvent, saponification reaction is carried out in a 0.5 mol / L NaOH solution at 80°C for 40 hours, centrifugation is performed to wash and separate, and vacuum drying is carried out at 40°C to constant weight to obtain a carboxyl precursor.

[0017] Furthermore, in step S3, the organic metal precursor of the carboxyl-substituted aluminoxane is prepared by the following method: the boehmite powder is ultrasonically dispersed in a toluene solvent to obtain a mixture, and then the carboxyl precursor obtained in step S2 is added to the mixture according to a molar ratio (COOH: Al = 0.5-2), and the mixture is heated under reflux for 3-8 hours. After the reaction is completed, the mixture is cooled to room temperature, filtered, washed with ether for 3-5 times, and vacuum dried to obtain an alumina precursor.

[0018] Furthermore, in step S3, the molar ratio of COOH:Al is 1-2.

[0019] Furthermore, the specific preparation method of the spherical nano-alumina in step S4 is as follows: the obtained alumina precursor is transferred into a muffle furnace for pyrolysis to obtain the spherical nano-alumina of the present invention.

[0020] Furthermore, the specific conditions for pyrolysis in step S4 are: a heating rate of 5-10°C / min, a pyrolysis temperature of 1200-1360°C, and a pyrolysis time of 8-12h.

[0021] The present invention adopts a one-step heating procedure to raise the temperature to the pyrolysis temperature. The spherical porous material will gradually decompose or carbonize from the outside to the inside, so that the organic substituents wrapped inside the porous material will slowly decompose. The organic segments or carbides produced by the decomposition can inhibit the excessive growth of alumina particles and reduce the transition temperature of the α-Al2O3 phase. That is, α-nano alumina can be obtained by calcining at a low temperature.

[0022] The present invention has the following beneficial effects:

[0023] 1. The present invention obtains a carboxyl precursor material by grafting carboxyl groups into a porous material. Relying on the large specific surface area of ​​the porous material, boehmite with a suitable particle size is adsorbed on the pore surface, and the aluminoxane precursor is replaced by carboxylic acid. The carboxyl precursor is decomposed or carbonized by a subsequent high-temperature pyrolysis step. The partially decomposed long-chain organic groups or their degraded carbides can inhibit the excessive growth of alumina particles and reduce the transition temperature of the α-Al2O3 phase, thereby obtaining spherical nano-α-Al2O3 with a size of 20-30nm.

[0024] 2. The carboxyl precursor of the present invention has the characteristic of adjustable pore size. The pore size distribution can be adjusted by adjusting the type and content of the porogen. The pore size of the precursor material can play a size screening role when adsorbing boehmite particles. That is, the present invention can achieve the effect of regulating the size of nano-alumina grains by regulating the pore size of the carboxyl precursor.

[0025] 3. The present invention limits the substitution reaction of boehmite and carboxyl to the pores of the carboxyl precursor. The physical isolation of the pores can largely avoid the agglomeration of nanopowders during the subsequent sintering process. In addition, the boehmite is adsorbed inside the pores. During the calcination process, the carboxyl precursor can be slowly and gradually decomposed from the outside to the inside, which helps to reduce sintering problems and adjust the size. Compared with the prior art, only one-step sintering is required, and no gradient temperature increase is required. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 IR spectra of the carboxyl precursor before and after hydrolysis in Example 2;

[0027] Figure 2 This is the pore size distribution diagram of the carboxyl precursor of Example 2;

[0028] Figure 3 This is the SEM spectrum of the nano-alumina prepared in Example 2;

[0029] Figure 4 The XRD spectrum of the nano-alumina prepared in Example 2; DETAILED DESCRIPTION

[0030] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments. The present invention can be implemented in many different forms and should not be construed as being limited to the embodiments set forth herein. On the contrary, these embodiments are provided so that this disclosure will be thorough and complete, and the concept of the present invention will be fully conveyed to those skilled in the art, and the present invention will only be limited by the claims.

[0031] Example 1

[0032] Suspension polymerization was carried out according to the mass ratio of oil phase to water phase of 1:3. The specific composition of the oil phase was 45g of divinylbenzene, 45g of methyl methacrylate, 0.5g of benzoyl peroxide, 270g of n-heptane, and the water phase was composed of 100g of 5% PVA solution and 980g of distilled water. The polymerization stirring speed was 300r / min, the polymerization temperature was 78°C, and the temperature was kept for 4h. After the reaction was completed, the spherical porous material was rinsed with ethanol. The spherical porous material was fully swollen in toluene, and after removing the solvent, it was saponified in 80°C, 0.5mol / L NaOH solution for 40h, centrifuged, washed and separated, and vacuum dried at 40°C to constant weight to obtain a carboxyl precursor. The carboxyl content of the carboxyl precursor was determined by conductivity titration to be 15.4mmol / g. The boehmite powder was ultrasonically dispersed in a toluene solvent to obtain a mixture, and then the carboxyl precursor was added to the mixture according to the molar ratio of COOH / Al=0.5, and stirred, heated under reflux for 8h, and cooled to room temperature. The obtained particles were filtered, washed with ether for 5 times, and finally vacuum dried to obtain an alumina precursor. The alumina precursor was transferred to a muffle furnace and heated to 1200°C at a heating rate of 10°C / min for pyrolysis for 8 hours to obtain the spherical nano-alumina of the present invention. After measurement, the average particle size of the nano-alumina in the present invention is 28nm.

[0033] Example 2

[0034] Suspension polymerization was carried out according to the mass ratio of oil phase to water phase of 1:3. The specific composition of the oil phase was 60g of divinylbenzene, 60g of methyl methacrylate, 0.55g of benzoyl peroxide, 300g of n-heptane, and the water phase was composed of 120g of 5% PVA solution and 1060g of distilled water. The polymerization stirring speed was 300r / min, the polymerization temperature was 78°C, and the temperature was kept for 6h. After the reaction was completed, the spherical porous material was rinsed with ethanol. The spherical porous material was fully swollen in toluene, and after removing the solvent, it was saponified in 80°C, 0.5mol / L NaOH solution for 40h, centrifuged, washed and separated, and vacuum dried at 40°C to constant weight to obtain a carboxyl precursor. The carboxyl content of the carboxyl precursor was determined by conductivity titration to be 14.8mmol / g. The boehmite powder was ultrasonically dispersed in a toluene solvent to obtain a mixture, and then the carboxyl precursor was added to the mixture according to the molar ratio of COOH / Al=1, and heated under reflux for 6h under stirring conditions, and cooled to room temperature. The obtained particles were filtered, washed with ether for 3 times, and finally vacuum dried to obtain an alumina precursor. The alumina precursor was transferred to a muffle furnace and heated to 1360°C at a heating rate of 10°C / min for pyrolysis for 8 hours to obtain the spherical nano-alumina of the present invention. After measurement, the average particle size of the nano-alumina in the present invention is 25nm.

[0035] Example 3

[0036] Suspension polymerization was carried out according to the mass ratio of oil phase to water phase of 1:3. The specific composition of the oil phase was 90g of divinylbenzene, 90g of methyl methacrylate, 1g of benzoyl peroxide, 540g of n-heptane, and the water phase was composed of 200g of 5% PVA solution and 1960g of distilled water. The polymerization stirring speed was 300r / min, the polymerization temperature was 76°C, and the temperature was kept for 6h. After the reaction was completed, the spherical porous material was rinsed with ethanol. The spherical porous material was fully swollen in toluene, and after removing the solvent, it was saponified in 80°C, 0.5mol / L NaOH solution for 40h, centrifuged, washed and separated, and vacuum dried at 40°C to constant weight to obtain a carboxyl precursor. The carboxyl content of the carboxyl precursor was determined by conductivity titration to be 13.9mmol / g. The boehmite powder was ultrasonically dispersed in a toluene solvent to obtain a mixture, and then the carboxyl precursor was added to the mixture according to the molar ratio of COOH / Al=2, and heated under reflux for 8h under stirring conditions, and cooled to room temperature. The obtained particles were filtered, washed with ether for 5 times, and finally vacuum dried to obtain an alumina precursor. The alumina precursor was transferred to a muffle furnace and heated to 1280°C at a heating rate of 10°C / min for pyrolysis for 8 hours to obtain the spherical nano-alumina of the present invention. After measurement, the average particle size of the nano-alumina in the present invention is 29nm.

[0037] Example 4

[0038] Suspension polymerization was carried out according to the mass ratio of oil phase to water phase of 1:3. The specific composition of the oil phase was 45g of divinylbenzene, 45g of methyl methacrylate, 0.5g of benzoyl peroxide, 270g of n-heptane, and the water phase was composed of 100g of 5% PVA solution and 980g of distilled water. The polymerization stirring speed was 280r / min, the polymerization temperature was 76°C, and the temperature was kept for 6h. After the reaction was completed, the spherical porous material was rinsed with ethanol. The spherical porous material was fully swollen in toluene, and after removing the solvent, it was saponified in 80°C, 0.5mol / L NaOH solution for 40h, centrifuged, washed and separated, and vacuum dried at 40°C to constant weight to obtain a carboxyl precursor. The carboxyl content of the carboxyl precursor was determined by conductivity titration to be 13.8mmol / g. The boehmite powder was ultrasonically dispersed in a toluene solvent to obtain a mixture, and then the carboxyl precursor was added to the mixture according to the molar ratio of COOH / Al=2, and heated under reflux for 8h under stirring conditions, and cooled to room temperature. The obtained particles were filtered, washed with ether for 4 times, and finally vacuum dried to obtain an alumina precursor. The alumina precursor was transferred to a muffle furnace and heated to 1200°C at a heating rate of 10°C / min for pyrolysis for 8 hours to obtain the spherical nano-alumina of the present invention. After measurement, the average particle size of the nano-alumina in the present invention is 24nm.

[0039] The specific surface area and pore analysis of the porous material prepared in the embodiment of the present invention are measured by low temperature (77K) nitrogen adsorption and desorption method. The sample needs to be pretreated with high-purity nitrogen before measurement, and the treatment condition is purging at 120°C for 13h. The BELSORP-mini II adsorption instrument measures the adsorption and degassing isotherms of nitrogen at 77K.

[0040] FT-IR was used to check whether the surface of the microspheres contained carboxyl functional groups. Conductometric titration was used to determine the carboxyl content of the microspheres. A microsphere dispersion with a certain solid content was first adjusted to a pH value of about 11 with a 10% NaOH solution, and then back-titrated with a 0.015 mol / L standard HCL solution under magnetic stirring, with 0.1 mL added every 30 seconds and the conductivity change recorded until the pH reached about 3. The microstructure of nano-alumina was analyzed using a SEM scanning electron microscope, the specific model of which was a JSM-6700F scanning electron microscope.

[0041] Figure 1 The infrared spectra of the carboxyl precursor before and after hydrolysis in Example 2 of the present invention are shown at 3474 cm -1 is the stretching vibration peak of OH in -COOH. It can be seen from the figure that the intensity and peak area of ​​the stretching vibration peak of OH in -COOH are improved to a certain extent after hydrolysis. In addition, 1700cm -1 The left and right are the absorption peaks of ester carbonyl. After hydrolysis, the peak height and peak area of ​​ester carbonyl are reduced to a certain extent, which also shows that the hydrolysis reaction is proceeding. Figure 2 This is a pore size distribution diagram of the porous material prepared in Example 2. It can be seen from the figure that the pore sizes of the porous material are mostly distributed between 50-100 nm. Figure 3 This is an electron microscope image of the nano-alumina prepared in Example 2 of the present invention. The nano-alumina material prepared in the present invention is spherical, and the average particle radius is 25 nm. Figure 4 This is the XRD spectrum of the nano-alumina obtained in Example 2 of the present invention. It can be seen from the figure that the alumina prepared in the present invention is an α-phase alumina material.

Claims

1. A method for preparing spherical Al2O3 nanoparticles at low temperature, characterized in that The steps include: S1: Preparation of porous materials; S2: Preparation of carboxyl precursors; S3: Preparation of alumina precursor; S4: The precursor is calcined to obtain spherical nano-alumina.

2. The method for preparing spherical Al2O3 nanoparticles at low temperature according to claim 1, characterized in that: The porous material in step S1 is prepared by suspension polymerization, and the mass ratio of oil phase to water phase in the suspension polymerization system is 1:

3.

3. The method for preparing spherical Al2O3 nanoparticles at low temperature according to claim 2, characterized in that: The polymerizable monomers in the oil phase are divinylbenzene and methyl methacrylate, the initiator is benzoyl peroxide, the porogen is n-heptane, the mass ratio of divinylbenzene to methyl methacrylate is 0.5-1:1, the amount of the initiator is 0.1-0.5% of the total mass of the polymerizable monomers, and the mass ratio of the porogen to the polymerizable monomers is 2-3:

1.

4. The method for preparing spherical Al2O3 nanoparticles at low temperature according to claim 2, characterized in that: The aqueous phase includes 5% PVA as a dispersant, and the weight of the dispersant accounts for 8-10% of the aqueous phase.

5. The method for preparing spherical Al2O3 nanoparticles at low temperature according to claim 2, characterized in that: The stirring speed of the suspension polymerization is 280-300 r / min, the polymerization temperature is 76-78° C., and the temperature is kept for 4-6 hours. After the reaction is completed, the spherical porous material is washed with ethanol to obtain the spherical porous material.

6. The method for preparing spherical Al2O3 nanoparticles at low temperature according to claim 1, characterized in that: The preparation method of the carboxyl precursor in step S2 is as follows: the spherical porous material obtained in step S1 is fully swollen in toluene, after removing the solvent, saponification reaction is carried out in a 0.5 mol / L NaOH solution at 80°C for 40 hours, centrifugation is performed to clean and separate, and vacuum drying is carried out at 40°C to constant weight to obtain a carboxyl precursor.

7. The method for preparing spherical Al2O3 nanoparticles at low temperature according to claim 1, characterized in that: The preparation method of the alumina precursor in step S3 is: ultrasonically disperse boehmite powder in toluene solvent to obtain a mixture, then add the carboxyl precursor obtained in step S2 to the mixture according to the molar ratio of COOH:Al=0.5-2, heat and reflux for 3-8h under stirring, after the reaction is completed, cool to room temperature and filter, wash with ether 3-5 times, and vacuum dry to obtain an alumina precursor.

8. The method for preparing spherical Al2O3 nanoparticles at low temperature according to claim 7, characterized in that; In step S3, the molar ratio COOH:Al=1-2.

9. The method for preparing spherical Al2O3 nanoparticles at low temperature according to claim 1, characterized in that: The specific preparation method of the spherical nano-alumina in step S4 is as follows: the obtained alumina precursor is transferred into a muffle furnace for pyrolysis to obtain the spherical nano-alumina.

10. The method for preparing spherical Al2O3 nanoparticles at low temperature according to claim 9, characterized in that: The specific conditions for pyrolysis in step S4 are: a heating rate of 5-10°C / min, a pyrolysis temperature of 1200-1360°C, and a pyrolysis time of 8-12h.

Citation Information

Patent Citations

  • A spherical alumina nanocrystal and its preparation method

    CN103663523B